Tecnologias da escrita: anotações digitais como estratégia de planejamento textual a partir do uso da plataforma DLNotes - Lima, Elane do Nascimento Brelaz de (2025)
This study investigates writing practices among students enrolled in the Language and Literature program at the Federal Technological University of Paraná (UTFPR), focusing on the relationship between notes taken during reading and the written production resulting from this practice. The research focused on the use of digital notes as a possible textual planning strategy, using the DLNotes tool, developed as part of the project “Computational strategies for reading, teaching, and learning in virtual environments in the field of Language and Literature” (CNPq 420520/2022-8). Based on the crisis in writing performance observed among Brazilian students, according to PISA 2024 data, the study seeks to understand how emerging technologies can mediate academic training and contribute to the qualification of writing in higher education. The methodology adopted involved analyzing responses to Question 4 of a form administered to 134 language arts students, which required a discursive production on the text read, with an emphasis on identifying and discussing the thesis defended by the author. Participants were encouraged to articulate their interpretations and analyses of the arguments presented, based on the use or non-use of notes—digital or printed—influencing the planning of their writing. The analysis is based on theoretical references that address the symbolic and cognitive role of writing (Cassirer, 2012; Hodges; Nobre), its completeness (Fischer, 2009), and the function of notes as a form of personal geography (Marshall; Brush, 2002). The results indicate that the use of digital notes can favor the organization of thought and allow the teacher to map the paths taken by the student in the process of writing development, making their argumentative structure and interpretive choices more visible. It was observed that technological mediation, combined with well-targeted pedagogical practices, such as the use of the DLNotes platform, can promote significant gains in the teacher/student relationship in the process of textual production. Given the scenario of increasing integration between digital literacy and teaching, the research is justified by the need to rethink pedagogical strategies that encourage more efficient, critical, and coherent writing practices, contributing to the formation of individuals who are better prepared for contemporary academic and professional challenges.